Enhancing the Effectiveness of the Zakat Management System to Reduce Taxable Income for Muslim Communities in East Java - Febriyanti , Novi (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2021)
In Muslim communities of East Java, taxpayers lack knowledge about the management, regulation, and calculation of zakat as a tax deduction. This gap in understanding impedes effective use of zakat funds for community improvement. Â Therefore, this study aimed to find out the challenges faced in implementing zakat management as a deduction from taxable income of Muslim communities in East Java and propose how to tackle them. A qualitative approach was used, focusing on analyzing phenomena in their natural setting. To get a comprehensive analysis of phenomenology related to the zakat management mechanism, data collection techniques, including observation, interviews, and documentation, were used. The results showed that the management of zakat as a deduction from taxable income involves zakat through official organizations recognized by the Government, including BAZNAS (National Board of Zakat) and LAZ (Zakat Collection and Distribution Organizations). Once the muzakki fulfill their tax obligations, they receive a zakat Payment Receipt (BSZ) that can be attached to the Tax return (SPT) when paying taxes. As a result, the taxable income is directly reduced by the actual amount of zakat paid, which can lead to tax savings. Low awareness of zakat payment, reluctance to pay zakat, and lack of complete trust in BAZNAS and LAZ organizations were the challenges encountered in implementing zakat deductions. Other challenges include a limited number of BAZNAS/LAZ organizations that are recognized by the government, insufficient socialization and education on Law No. 23 of 2011 regarding zakat management, less significant tax reduction, and differences in interpretation when calculating the deduction of taxable income on zakat income.